Black Suffering for/from Anti-trafficking Advocacy - Beutin, Lyndsey P. (Anti-Trafficking Review, 2017)
This article analyses the images that Antislavery Usable Past creates to promote its cause of ‘making the antislavery past usable for contemporary abolition’. Drawing on collective memory studies, I discuss the political implications of how pasts are used for present issues. I argue that Antislavery Usable Past appropriates black suffering by reducing the memory and imagery of slavery to objects that are compatible with the anti-trafficking narrative, without regard for the ongoing black liberation struggle. I conclude by discussing the troubling trend of incorporating anti-trafficking exhibitions into institutions that preserve the history of slavery and abolition. Such inclusions redirect the history lessons of slavery away from understanding and addressing anti-blackness in the present and towards supporting advocacy campaigns articulated in the logics that underpinned racial chattel slavery in the first place.